Design, implementation, and evaluation of an online instructional process to enhance teachers’ design thinking skills - Yeşim Sürmelioğlu; Mukaddes Erdem (Humanities & Social Sciences Communications)
Abstract This study aimed to design an online, collaborative, project-based environment and process based on constructivist learning to enhance teachers’ design thinking skills and to test the effectiveness of the application. In the study, design thinking skills were tried to be developed online with processes based on scenario writing and animation. Since there is a need for interdisciplinary collaborative work due to the nature of design thinking, the study was carried out with a sample consisting of 7 history teachers, 7 geography teachers, and 8 social studies teachers. A total of 1080 min of online project-based design thinking teaching was given to teachers by the researcher for 12 days, 90 min per day. The study was designed with an embedded complex mixed methods research design. In the study, quantitative data were collected at the beginning and end of the implementation, while qualitative data were collected before, during, and at the end of the implementation. The designed design thinking teaching process was successfully carried out within the scope of the constructivist learning approach, in an online learning environment, in a project-based teaching process, by applying learning practices. At the end of the process, contributions were observed in terms of professional development, such as a roadmap for design thinking, project ideas, interdisciplinary and teamwork. The processes and outcomes of the research have contributed to the development of an instructional design grounded in design thinking.